Comparing Orphanges' Hope and Loneliness as Lifelong Learners in Tanjung Barat Orphanage South Jakarta - Anastasia Dewi Anggraeni (LPPM Universitas Pendidikan Mandalika, 2020)
This research aims to compare the loneliness and hope among orphans in the Tanjung Barat orphanage, South Jakarta. The research method used a descriptive qualitative with a case study method. Data collection techniques were interviews, observations, and filling in a simple questionnaire. The sample used 36 children of Tanjung Barat orphanage consisting of elementary school, junior high school and senior high school students. This was done on site and compared to the literature that had been previously established.  Comparing loneliness and hope among orphans aimed to identify and find ways of mapping loneliness and hope among orphans who had been explored and investigated empirically, to find out the comparison and contrast with the mapping of loneliness and hope expressed among them, and to find examples of self-assessment to evaluate and encourage the mapping of their loneliness and expectations among them and present them to caregivers, parents and professionals. By comparing their loneliness and hopes they can actively engage in social interaction between themselves, others, and improve their personal, welfare and life skills.